2020
DOI: 10.1016/j.apacoust.2019.107182
|View full text |Cite
|
Sign up to set email alerts
|

Numerical prediction and experimental validation of impact sound radiation by timber joist floors

Abstract: Timber joist floors are widely applied in residential buildings. The accurate prediction of the sound radiated by timber joist floors is challenging due to the interaction between the impacting mass and the floor, orthotropy of the joist and plate components, the effects of the floor size and boundary conditions, etc. In the present work, state-of-the-art approaches for the prediction of impact forces, structural vibration, and radiated sound power were combined into a prediction method for the sound pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Here, uncertainty is introduced in the simulation model since the damping value proposed by Eurocode 5 [36] applies to low frequencies related to vibrations. A timber joist floor investigated by Wang et al [38] showed an approximate structural loss factor of 0.02 up to 2500 Hz. Although this work deals with a pure timber instead of a hybrid steeltimber floor, the chosen loss factor of 0.02 is deemed acceptable as a first estimate, as currently, no investigations exist on the impact sound behavior of hybrid steel-timber floors such as the presently studied ones.…”
Section: Model For Vibroacoustic Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, uncertainty is introduced in the simulation model since the damping value proposed by Eurocode 5 [36] applies to low frequencies related to vibrations. A timber joist floor investigated by Wang et al [38] showed an approximate structural loss factor of 0.02 up to 2500 Hz. Although this work deals with a pure timber instead of a hybrid steeltimber floor, the chosen loss factor of 0.02 is deemed acceptable as a first estimate, as currently, no investigations exist on the impact sound behavior of hybrid steel-timber floors such as the presently studied ones.…”
Section: Model For Vibroacoustic Validationmentioning
confidence: 99%
“…Furthermore, the driving-point impedance of the floor is computed from the local Z L and global impedance Z G as follows [38]: with the maximum walking frequency f w = 1.8 Hz and the considered eigenfrequencies f m 3: Compute peak velocity in each mode m: vm ¼ U e;m U r;m I eff;m = mm with U e,m the value of the mode shape m at the excitation position, U r,m the value of the mode shape m at the receiving position, mm the modal mass of mode m 4: From this, calculate the velocity response in each mode over the period of one footfall T with f as the modal damping ratio:…”
Section: Impact Soundmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the interaction of the impact source and the floor was demonstrated which manifests itself especially in the case of light ceilings or reactive floors [4,5]. Ongoing verification and development of effective prediction models with the focus on footfall noise is underway [6,7]. The work of Roozen et al…”
Section: Introductionmentioning
confidence: 99%
“…In case of wooden floors, general models describing the interaction between the STM and the floor have previously been presented by Amiryarahmadi et al [8], Brunskog and Hammer [5], Coguenanff et al [9], Rabold et al [10], and Wittstock [11]. In the recent decades, the use of the finite element method (FEM) to compute impact sound insulation of wooden floors has raised interests [12][13][14][15][16]. Thus, an appealing procedure would be to compute the impact force excitation by using a FEM tool.…”
Section: Introductionmentioning
confidence: 99%